Tsunami Potential Due To Strike-Slip Earthquake Affected by Submarine Landslide - Wiko Setyonegoro (BULLETIN OF THE MARINE GEOLOGY, 2016)
The most of earthquakes in the western part of North of Sumatra, Indonesia have tsunami potential. This paper discuss about tsunami height which was triggered by large energy of earthquake along strike-slip fault and submarine landslide. Beyond of a view historical tsunamis in the western part Sumatra in Aceh, which was occured on April 11, 2012 have given several questions for the majority of earth scientist in relation with the potential for tsunami. The 8.6 M earthquake might have no tsunami potential significantly, with the hypothesis that mechanism of the earthquake source is strike-slip. However BMKG, in accordance with standard operating procedures stated that this earthquake "potential tsunami". But here we will give other parameters that affect a potential tsunami by performing the calculation of the effects of landslides. This paper describes how potential and kinetic energy spread during landslide and analysis of mechanism and underwater structures named as guyot as the cause of the earthquake along strike-slip fault. This paper discuss about scoup study on landslide which give the hypothesis that the type of submarine landslide or landslide of near shore cliff also will have influence to tsunami height or run-up. The key is, how strongly the all of disturbance above will increasing or decreasing ofÂ  sea water volume. The result for the first case, strike-slip earthquake without the submarine landslide obtain maximum run-up in Meulaboh  is 1.5864 m, with E~Mo (seafloor deformation). For the second case is strike-slip earthquake influenced by submarine landslide obtained ETotal ~1020 ~ Mo (seafloor deformation) which obtained tsunami run-up in Meulaboh 1.7726 m. So in this case, the landslide under the sea it also affected to the maximum tsunami height, but not significantly influence. For the last case, strike-slip earthquake influenced by landslide of near shore cliff: ETotal is estimated Ekfall ~  1022  ~  Mw ~  8 SR, equivalent with vertical of seafloor deformation and obtain tsunami run-up in Meulaboh 16.9372 m.Keywords: tsunami run-up, fault, strike-slip, submarine landslide, uppper the sea landslide, potential energy, kinetic energySebagian besar gempabumi yang terjadi pada area barat Sumatera Indonesia berpotensi tsunami. Tulisan ini memodelkan kemungkinan ketinggian tsunami yang dipicu oleh gempabumi dengan energi besar sepanjang sesar geser yang dipengaruhi oleh longsoran bawah laut. Gempabumi dengan kekuatan 8,6 Mw pada 11 April 2012 yang terjadi di bagian barat Sumatera telah menimbulkan kepanikan akan tetapi tidak menimbulkan bencana tsunami besar karena terjadi di sepanjang sesar geser kerak Samudera Hindia. Berdasarkan pemodelan, gempabumi sepanjang sesar geser dapat memicu tsunami besar bilamana diikuti oleh longsoran bawah laut. Tujuan dari penelitian ini adalah untuk memodelkan propagasi gelombang tsunami dengan proses mekanisme gempabumi strike-slip yang dipengaruhi oleh kondisi batimetri, volume struktur, jumlah dan jenis tanah longsor bawah laut yang dapat memicu ketinggian gelombang tsunami. Perhitungan dan pemodelan ini melibatkan simulasi energi potensial dan energi kinetik yang mempengaruhi ketinggian gelombang tsunami pada garis pantai. Hasil pemodelan pertama, dengan anggapan gempabumi sesar geser yang tidak dipengaruhi oleh proses longsor bawah laut menghasilkan ketinggian tsunami di Meulaboh 1,5864 m, dengan E ~ Mo (deformasi dasar laut). Untuk kasus pemodelan kedua dengan anggapan gempabumi sesar geser disertai oleh longsoran di bawah permukaan laut diperoleh Etotal ~ 1020 ~ Mo (deformasi dasar laut) yang menghasilkan ketinggian tsunami di Meulaboh 1,7726 m. Untuk pemodelan ketiga, gempabumi sesar geser yang diikuti oleh longsoran di tebing dekat pantai dengan Etotal diperkirakan Ekfall ~ 1022 ~ Mw ~ 8 SR setara dengan jenis mekanisme deformasi vertikal yang dapat menghasilkan ketinggian gelombang tsunami di Meulaboh sampai dengan 16,9372 m. Kata Kunci: run-up tsunami, sesar geser, longsoran bawah laut, longsoran diatas permukaan laut, energi potensial, energi kinetik